(untitled) (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
Pierre Samson (1958) draws a map of desire that crosses Brazil and blurs the boundaries of time. In Le Messie de Belém (1996), Un garçon de compagnie (1997) and Il était une fois une ville (1999), he shows a world crossed by the forbidden and violence, the force of the past haunting the present. Beneath the thin film of history, Samson offers the reader the map of our passions, and beneath Brazil, both real and imaginary, he reveals the elsewhere that hides and reveals itself within us all. It seems to me that Samson is trying to show the strength of desire, its capacity to cross prohibitions, ages, groups. At a first reading, one can easily hear echoes of Gide, Genet, and perhaps Foucault as well, the last volumes of his Histoire de la sexualité. In many aspects, Samson is nostalgic for a world where passions are not subject to law, norms and judgement. It is no coincidence that desire is less and less in evidence when it leaves the Brazilian space. In the Brazilian trilogy, but also in La maison des pluies (2013) and L’œil de cuivre (2015) the same themes return with force and the informed reader cannot fail to notice the insistence with which Samson uses water as an element capable of framing the representation of desire. Rivers, ponds, natural pools abound in the Brazilian trilogy: immersed in water, the characters do not impede their desires. In La maison des pluies and L’œil de cuivre, water is present in the form of rain, sweet and melancholic. In my paper I would like to explore this cartography of desire and this natural element with multiple functions; to do so I will use Gaston Bachelard’s study, L’eau et les rêves, on the one hand, and Dosse’s recently published study Les vérités du roman on the other.